Ethnomathematics at TIFA Yapen as A Source for Learning Mathematics - Yeni D. Fonataba; Ronaldo Kho; Bettisari Napitupulu; Irfan Wahyudi; Happy Lumbantobing (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2023)
This study's primary objective is to investigate and elucidate the principles and regulations of ethnomathematics prevalent in the Yapen Islands of Papua, Indonesia, for application in the context of mathematics education in schools. The research methodology involves qualitative research with an ethnographic approach. Data was collected through participant observation techniques and in-depth interviews, and the subsequent data analysis followed a sequence of ethnographic data analysis, domain analysis, and taxonomic analysis. The findings of this research indicate that precise measurements of the tifa's length and width significantly affect the sound (tone) produced when the tifa is struck. The design aspect involves the ability to elucidate the steps and sequence involved in crafting a tifa, ensuring clarity and comprehensibility in the explanation. Furthermore, the ability to explain extends beyond comprehending the manufacturing process to effectively communicating it to the general public. The geometric patterns observed on the tifa include circular shapes on the lid and base, a prism shape near the tifa cover, an isosceles trapezoid shape on the tifa handle, and a parallelogram shape on the tifa handle.